Pengaruh Model Problem Based Learning Terhadap Hasil Belajar PPKn Pada Murid Kelas V SD Pangkabinanga Kecamatan Pallangga Kabupaten Gowa - Attissa, Ikkera; Nawir, Muhammmad; Said, Try Gustaf (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study aims to determine the effect of the Problem Based Learning model on PPKn learning outcomes in grade V students of Pangkabinanga Elementary School, Pallangga District, Gowa Regency. The type of research used in this study is experimental research, especially Pre-experimental. The sample in this study was 25 students. Data collection techniques were carried out using learning outcome tests and observation sheets. Data analysis techniques in this study were descriptive data analysis techniques and T-Test tests. The results of the study showed that PPKn learning outcomes before the implementation of the Problem Based Learning model in the pretest with an average value of 65.2. While in the posttest increased with an average value of 94.8. The results of the t-test analysis on the effect of the Problem Based Learning model on student learning outcomes showed that the significance value obtained was good, namely the effect of the Problem Based Learning model on PPKn learning outcomes (Sig = 0.01) was smaller than the specified alpha value of 0.05 (0.01 <0.05). Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted, which states that there is an influence of the Problem Based Learning model on the learning outcomes of PPKn students in grade V of Pangkabinanga Elementary School, Pallangga District, Gowa Regency.